Metonymy and frame integration: Interfacing between concepts and discourse - Ioannou Georgios (Topics in Linguistics, 2019)
This article inquiries into specific aspects of the relation between conceptual contiguity found in metonymic shifts and the online construction of frames, seen as a dynamic process of construal. It first reviews the theory of metonymy regarding the conceptual, lexical and contextual facets of the phenomenon. It then explores the possibility of extending the conceptual relevance of metonymy beyond the traditional typological approach of metonymic categorization, re-interpreting it as a frame-integration mechanism, or blending, whereby two frames are brought together into an extended ICM. Metonymic blending is formulated as a partial integration between two input spaces discursively driven, whereby an ad hoc identification of a referential commonness plays the role of the generic space of the blending. Subsequently, in the light of the assumption that frame-extension is not given categorically but it also includes – beyond its cognitive relevance – an interactional aspect, this analysis draws an interesting link: that between the generic space of metonymic blend, and common ground. The latter is precisely what facilitates the metonymic blend, regulating the distance between the integrated frames, at the same time remaining silent as discursively given information.